Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME